1969
DOI: 10.1111/j.1651-2227.1969.tb04696.x
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐base and Electrolyte Balance in Newborn Infants of Diabetic Mothers

Abstract: Summary The acid‐base and electrolyte balance was studied in 8 diabetic and 8 healthy mothers and their infants at caesarean section near term. Microliter methods were used for determination of pH, total CO2, potassium, sodium, chloride, calcium, total protein, inorganic phosphorus, glucose and lactate. The acid‐base and electrolyte balance of the newborn infant of a well‐controlled diabetic mother did not differ significantly from that of a newborn infant of a healthy mother. The infant of a diabetic mother s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1971
1971
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The minimum level found by us is in agreement with recent reports (7,28). Several investigators (for references, see 5 , 26) have found that total plasma calcium in umbilical cord is higher than in maternal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The minimum level found by us is in agreement with recent reports (7,28). Several investigators (for references, see 5 , 26) have found that total plasma calcium in umbilical cord is higher than in maternal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…
In a previous paper the acid-base and electrolyte balance was studied in infants of diabetic mothers at caesarean section (16). It was found that these infants did not differ significantly in their acid-base and electrolyte balance from healthy infants at birth.After birth, hypocalcaemia and hyperphosphataemia have been observed by several investigators (3, 6, 21), but on the other hand "normal" values of potassium, sodium and chloride have been found (20).
…”
mentioning
confidence: 97%
“…In a previous paper the acid-base and electrolyte balance was studied in infants of diabetic mothers at caesarean section (16). It was found that these infants did not differ significantly in their acid-base and electrolyte balance from healthy infants at birth.…”
mentioning
confidence: 97%
“…The acid-base and electrolyte balance in infants of diabetic mothers (IDM), delivered by caesarean section, has previously been studied at birth and during the first 48 hours after birth (13,15). At birth the acid-base balance of IDM was similar to that of infants of healthy mothers (IHM), but in the early neonatal period the IDM had slightly higher pHvalues and lower levels of Pcoz and plasma potassium than the IHM.…”
mentioning
confidence: 99%